CRIMINAL DEFAMATION IN FIQH JINAYAH - Erha Saufan Hadana (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2020)
This paper specifically discusses the crime of defamation in the scope of fikih jinayah, this discussion was chosen because the act is considered an act that can damage a person's honour, so it needs to be criminalised in the context of fikih jinayah. This discussion is important to identify, map and develop the concept of thought in fikih jinayah regarding the criminal act of defamation. This study is based on literature data which is analysed descriptively. The results of the study show that defamation should be criminalised in jurisprudence, because it damages a person's honour, based on the obligation to protect honour (al-'irāḍ) which is included in the maqāṣid objectives of the sharī'ah and based on the interpretation of scholars regarding the expansion of the meaning of yarmūn in Surah an-Nūr verse 4.